Wolfram alpha como herramienta didáctica en la enseñanza de ecuaciones lineales en estudiantes de primero bachillerato general unificado de la Unidad Educativa Guaranda periodo 2024- 2025 - Álvarez Guamán, Andrés Alejandro (2025)
This research focuses on the use of TICs, specifically the Wolfram Alpha program, as a teaching tool for linear equations, aimed at first-year high school students at Unidad Educativa Guaranda. The main objective is to apply Wolfram Alpha as a didactic tool in teaching linear equations to improve students' academic performance. Specific objectives include creating a teaching guide for using Wolfram Alpha in the learning process of linear equations and providing continuous training on the tool. Additionally, a diagnostic assessment is performed before and after using the program. To achieve these objectives, an in-depth study was conducted on the lack of knowledge among students about using technological-didactic tools for learning linear equations. Based on this, a step-by-step guide was created to train students on using Wolfram Alpha, with the goal of diagnosing any cognitive development improvements. The study demonstrates that this tool offers an innovative approach, contributing to a futuristic education model